Comparative Studies of Employability in Higher Education: Private University and Public University - Anissa Lestari Kadiyono; Nisrina Budiana Putri (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to compare the employability of final-year students at public universities and private universities so that it can provide an overview to prospective students or the Ministry of Education on the quality of graduates as future worker generations. The research design used is non-experimental quantitative, with 92 students from public universities and 93 students from private universities as the subject. The study used a two-stage cluster random sampling data collection technique. Data were collected based on the employability theory of Dacre Pool (2007). A comparison of employability was calculated using a t-independent test for two independent samples. The results show no significant difference in employability between final-year students at public and private universities. As many as 77% of final-year students in public universities and 76% of final-year students in private universities have employability which tends to be high, which means they tend to have the knowledge, understanding, skills, and personal attributes that can make them feel satisfied and successful in his work. However, there are differences in work readiness patterns, where state university students have the lowest score on the experience dimension, while private university students get the lowest score on the degree subject knowledge dimension. This study requires further explanation on this matter in order to obtain further answers regarding the work readiness of university graduates.